Yersinia pseudotuberculosis colitis presented with severe gastrointestinal bleeding - BÜLBÜLOĞLU, ERTAN; Bulbuloglu, ERTAN; Ciralik, Harun; Kantarceken, Bulent; Cetinkaya, Ali; Gul, Mustafa; Ezberci, Fikret (My University, 2010)
We report an adult case of Yersinia pseudotuberculosis colitis who presented with severe gastrointestinal bleeding. A 25-year-old male had admitted with fever, vomiting, body aches, and massive lower gastrointestinal bleeding. Since diagnostic tests were unremarkable and the patient-s hemodynamic condition was unstable, emergency explorative laparotomy was performed. During the operation, localized wall thickening and ulcers were seen in the cecum. Right hemicolectomy was performed. Histological examination showed non-caseation granulomas in mesenteric lymph nodes and transmural inflammation in the cecum. Y. pseudotuberculosis serology, based on histological suspicion, was positive. The patient was discharged with cure 12 days after the operation following gentamicin treatment. To our knowledge, there are only two reports about massive lower gastrointestinal bleeding due to Y. pseudotuberculosis. Although this is a rare entity, lower gastrointestinal bleeding due to Y. pseudotuberculosis should be taken into consideration in the differential diagnosis of patients presenting with massive lower gastrointestinal bleeding, as a possible cause.